1991
DOI: 10.1159/000186411
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Region-Wide Hepatitis B Vaccination Program in Dialysis Patients: Experience in an Italian Region

Abstract: In 1985-1986, 634 adult dialysis patients were tested prior to hepatitis B vaccination, representing 40% of the total patients in Latium, an Italian region. HBsAg and anti-HBs prevalences were 7.1 and 36.0%, respectively. Merck, Sharp & Dohme (MSD) and Pasteur plasma-derived vaccines were randomly allocated to the 44 dialysis units. An anti-HBs response greater than or equal to 10 IU/l was elicited in 58.5% of 236 subjects tested at 6 months, 63.4% MSD and 52.4% Pasteur (p n.s.). The relatively low response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…Albertoni et al reported a sharp increase in HbsAg carriers in patients with 10 years or more of hemodialysis, a nding they attributed to a cohort effect. 34 In our study demonstrate a markedly higher HBV prevalence in patients with 3 years or more of hemodialysis ( Figure 1). The positive association between HBV prevalence and years of hemodialysis has several possible e planations.…”
Section: Discussionsupporting
confidence: 56%
“…Albertoni et al reported a sharp increase in HbsAg carriers in patients with 10 years or more of hemodialysis, a nding they attributed to a cohort effect. 34 In our study demonstrate a markedly higher HBV prevalence in patients with 3 years or more of hemodialysis ( Figure 1). The positive association between HBV prevalence and years of hemodialysis has several possible e planations.…”
Section: Discussionsupporting
confidence: 56%
“…A variety of approaches have been tried to enhance the response rate of HB vaccination in dialysis patients: the intramuscular administration of double doses [106,[109][110][111][112][113][114][115][116] or multiple doses [106,113,[117][118][119][120][121][122][123][124], intradermal inoculation [125][126][127][128][129][130][131], the combined use of the intramuscular and intradermal routes [132]. Inclusion of a more extended portion of the HBV genome containing the pre-S2 protein in the vaccine might increase the response rate [133][134][135].…”
Section: Hbv Vaccination In Dialysis: Short-term Studiesmentioning
confidence: 99%
“…Introduction of HBV vaccination, isolation of HBV positive patients, use of dedicated dialysis machines and regular surveillance for HBV infection has dramatically reduced the spread of HBV in this setting [6][7][8][9][10] . However, the frequency of HBV infection in patients undergoing maintenance dialysis in the industrialized world is low, but not negligible [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%